Assessment of Stone Ash as a Lightweight Concrete Material with the Addition of Bestmittel Additives - Budiman, Budiman; Tiranda Patanduk, James Williams (EPI International Journal of Engineering, 2023)
Technological advances in the field of building construction have developed very rapidly, so we need a construction technology that can reduce exploitation of nature. Utilization of stone ash is one of the new material alternatives in concrete mixtures with the addition of the bestmittel additive to accelerate drying in concrete. The purpose of this study is to determine the aggregate characteristics, specific gravity and compressive strength of concrete. The method used is laboratory experimental research with variations in stone ash samples of 5%, 10% and 15% to the weight of sand with the addition of 0.6% bestmittell additive to the weight of cement. The results showed that stone ash and bestmittell additives affect the characteristics of the concrete. The value of specific gravity increases with increasing percentage of stone ash, namely 1898.77 kg/m3 in normal concrete, 1911.35 kg/m3 of 5% stone ash concrete, 1922.34 kg/m3 of 10% stone ash concrete and 1927.06 kg/m3 m3 on 10% stone ash concrete. The compressive strength value of characteristic for the compositions AB 5%, AB 10% and AB 15% are 10.08 Mpa, 10.35 Mpa and 10.88 Mpa respectively, an increase compared to normal AB 0% concrete, namely 9.03 Mpa at 28 days.